Spatially correlated exit strategies in the baking industry (2007)
This article uses a unique data set to analyse economic factors that explain firm exit and the interrelation across firms in space when exiting. Results show the effectiveness of modelling spatial correlation in a logit exit model. Indeed, in our application, reliable statistical results could only be drawn from our data when including spatial correlation in the model.